Psychometric Properties of the Impact of Events Scale-Revised (IES-R) Among General Iranian Population During the COVID-19 Pandemic - Sharif Nia, Hamid; Kaur, Harpaljit; Fomani, Fatemeh Khoshnavay; Rahmatpour, Pardis; Kaveh, Omolhoda; Pahlevan Sharif, Saeed; Venugopal, A. Vijayalakshmi; Hosseini, Lida (Frontiers in Psychiatry, 2021)
Objective: The aim of this study was to translate and evaluate the validity and reliability of the Impact of Events Scale-Revised (IES-R) among the Iranian general population during the COVID-19 pandemic. Method: This study was methodological cross-sectional. It was conducted on an Iranian public population from April to July 2020 which was during the COVID-19 pandemic. Construct validity was determined through Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA) with a total of 500 adults, recruited via online data gathering. Reliability was checked through the Average Inter-Item Correlation (AIC), Cronbach’s alpha, and McDonald’s omega. Convergent and divergent validity was determined using Fornell and Larcker’s approach. Results: The results showed that the Persian version of IES-R had three factors, including intrusion (6 items), avoidance (7 items), and hyperarousal (5 items), which explained 59.22% of the total variance of the IES-R. The CFA findings indicated that all goodness of fit indices confirmed the model fit. The Cronbach’s alpha, McDonald’s omega, Composite Reliability (CR), and maximal reliability were excellent and the three factors have good convergent validity. Conclusion: The findings of this study indicated that the Persian version of the IES-R scale is efficient and useful to assess Post-Traumatic Stress Disorder among Iran general population in the COVID-19 outbreak.